2017
DOI: 10.1002/jssc.201601399
|View full text |Cite
|
Sign up to set email alerts
|

Long‐chain ionic liquid based mixed hemimicelles and magnetic dispersed solid‐phase extraction for the extraction of fluorescent whitening agents in paper materials

Abstract: A novel mixed hemimicelles and magnetic dispersive solid-phase extraction method based on long-chain ionic liquids for the extraction of five fluorescent whitening agents was established. The factors influenced on extraction efficiency were investigated. Under the optimal conditions, namely, the pH of sample solution at 8.0, the concentration of long chain ionic liquid at 0.5 mmol/L, the amount of Fe O nanoparticle at 12 mg, extraction time at 10 min, pH 6.0 of methanol as eluent, and the desorption time at 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Hydrophobic ILs can be collected after the addition of the magnetic material due to the electrostatic interactions between the IL cation and the negatively-charged surface of the MPs [84][85][86][87][88][89]. Furthermore, despite the hydrophilicity of IL-based surfactants, they form mixed hemimicelles (hemimicelles plus admicelles) on the surface of MPs due to electrostatic interactions, thus functionalizing these MPs to improve their extraction efficiency [90,91]. The formation of hemimicelles as a monolayer of IL provided hydrophobic interactions, while the bilayer of admicelles provided more electrostatic interactions between the sorbent and the target analytes.…”
Section: Magnetic Effervescent Tablets and Other Strategies Based On ...mentioning
confidence: 99%
“…Hydrophobic ILs can be collected after the addition of the magnetic material due to the electrostatic interactions between the IL cation and the negatively-charged surface of the MPs [84][85][86][87][88][89]. Furthermore, despite the hydrophilicity of IL-based surfactants, they form mixed hemimicelles (hemimicelles plus admicelles) on the surface of MPs due to electrostatic interactions, thus functionalizing these MPs to improve their extraction efficiency [90,91]. The formation of hemimicelles as a monolayer of IL provided hydrophobic interactions, while the bilayer of admicelles provided more electrostatic interactions between the sorbent and the target analytes.…”
Section: Magnetic Effervescent Tablets and Other Strategies Based On ...mentioning
confidence: 99%
“…The authors exploited the adsorption of the [C 16 MIM + ][Br − ] IL to magnetic graphene oxide to extract the studied chlorophenols and optimized extraction conditions resulting in E F greater than 400 for aqueous solutions at 20 ppb. Wang and coworkers developed a MSPE method based on the adsorption of the same [C 16 MIM + ][Br − ] IL to a magnetic substrate to facilitate the extraction of fluorescent whitening agents in paper samples .…”
Section: Il‐based Materials In Magnetic Solid‐phase Extractionmentioning
confidence: 99%
“…[ 25 ] There are many kinds of substances in printing paper, including fluorescent whitening agent (FWA) added in the production process. [ 26,27 ] Moreover, a survey in the United Kingdom has reported that high FWA concentrations (430–1160 mg/kg paper) were detected in some napkins and paper materials used for ‘take‐out’ food packages. [ 28,29 ] It is well known that waste paper recycling significantly reduces environmental pollution and decreases waste flow to the environment and associated disposal costs.…”
Section: Introductionmentioning
confidence: 99%